Nové možnosti TDM cyklosporinu A a jeho metabolitů po transplantaci ledvin - Grundmann, Milan (Iga MZ ČR, 2010)
Cyklosporin A (CsA) is the major imunossupresive drug for organ transplantations. Optimal immunossupresive effect so as reduction of adverse effects is done through terapeutic monitoring of CsA levels (TDM). Methods used for estimation of CsA level in blood are not sufficiently specific and cross reactions with CsA metabolites cause significant differences to compare with real levels. Developed HPLC metod can analyse CsA and main metabolites AM1, AM9, AM4N. This metod was used for TDM in blood and in lymphocytes as the target organ of immunossuprese. Aim of our investigation is to compare TDM CsA and its metabolits in C through, C2 and AUC in blood and in lymphcytes during long time administration. New renal transplant patients will be observed (25/year)and so as pacients long term stable (300). Correlation TDM, clinical status and markers of immunosuppression (IL-2,IMG) could find, whether TDM in lymphocytes is more convenient than TDM in blood.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: lymfocyty; imunosupresiva; cyklosporin; Kidney Transplantation; Lymphocytes; rejekce štěpu; transplantace ledvin; nefrologie; Graft Rejection; Immunosuppressive Agents; farmacie a farmakologie; Cyclosporine